الجرائم الانتخابية في التشريع الجزائري - (:unkn) unknown (University of Eloued جامعة الوادي, 2017)
الإنتخاب هو وسيلة هامة للوصول إلى السلطة وهو اللآلية الأمثل للتعبير عن الإرادة الشعبية الحقيقية، ولكن قد تحصل انتهاكات وتجاوزات لهذه الوسيلة مما يؤدي إلى ظهور الجرائم الانتخابية التي هي عنوان مذكرتي هذه.والتي قسمتها إلى فصلين، تناولت في الفصل الاول الجرائم الخاصة بالمرحلة التمهيدية للعملية الانتخابية أما في الفصل الثاني فتطرقت فيه لدراسة الجرائم المتعلقة بالمرحلة المعاصرة واللاحقة للعملية ألانتخابية وخلصت في الأخير إلى أن المشرع الجزائري قد سلط الضوء على جل الأفعال الماسة بالعملية الانتخابية من خلال تجريمه لها إلا أنه توجد بعض الأفعال لم يجرمها بالرغم من مساسها لنزاهة وشفافية هذه العملية الانتخابية.واستنتجت في الاخير أن الواقع العملي هو المرآة الحقيقية لشفافية ونزاهة العملية الانتخابية ولا يتحقق هذاإلا بوعي الهيئة الناخبة عند تطبيقها للقوانين .The election is an important means of reaching power, which is the best mechanism for expressing the true popular will. However, violations and abuses of this method may occur, leading to the emergence of the electoral crimes which are the title of this memorandum. The second chapter deals with the crimes related to the contemporary and post-electoral processes and concluded that the Algerian legislator has highlighted most of the actions that are harmful to the electoral process by criminalizing them. However, Despite its prejudice to the integrity and transparency of this electoral process. Finally, it concluded that the practical reality is the true mirror of the transparency and integrity of the electoral process, and this can not be achieved without the awareness of the electorate when applying the laws.
مدكرة ماستر
Keywords: العملية الانتخابية ، الركن المادي والركن المعنوي ، الجريمة الانتخابية ، الانتخابات ، الهيئة الناخبة: The electoral process, the physical and moral pillar, electoral crime, elections, the electoral body